2013
DOI: 10.1073/pnas.1219908110
|View full text |Cite
|
Sign up to set email alerts
|

Rules that govern UPF1 binding to mRNA 3′ UTRs

Abstract: Nonsense-mediated mRNA decay (NMD), which degrades transcripts harboring a premature termination codon (PTC), depends on the helicase up-frameshift 1 (UPF1). However, mRNAs that are not NMD targets also bind UPF1. What governs the timing, position, and function of UPF1 binding to mRNAs remains unclear. We provide evidence that (i) multiple UPF1 molecules accumulate on the 3′-untranslated region (3′ UTR) of PTC-containing mRNAs and to an extent that is greater per unit 3′ UTR length if the mRNA is an NMD target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
120
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(133 citation statements)
references
References 38 publications
(66 reference statements)
8
120
0
1
Order By: Relevance
“…Consistent with previously observed preferential steady-state association of UPF1 with NMD targets (Johansson et al 2007;Johns et al 2007;Silva et al 2008;Hwang et al 2010;Kurosaki and Maquat 2013;Lee et al 2015), the top 1000 significant NMD targets are overall enriched in UPF1 CLIP tags (Supplemental Fig. S6), demonstrating a strong correlation between the two data sets.…”
Section: Identified Nmd Targets Show Expected Propertiessupporting
confidence: 86%
“…Consistent with previously observed preferential steady-state association of UPF1 with NMD targets (Johansson et al 2007;Johns et al 2007;Silva et al 2008;Hwang et al 2010;Kurosaki and Maquat 2013;Lee et al 2015), the top 1000 significant NMD targets are overall enriched in UPF1 CLIP tags (Supplemental Fig. S6), demonstrating a strong correlation between the two data sets.…”
Section: Identified Nmd Targets Show Expected Propertiessupporting
confidence: 86%
“…Cryo-EM structures of the exon junction complex (EJC)-UPF complex have positioned Upf1 on the 3 ′ side of the EJC (Melero et al 2012), contradictory to the current notion of Upf1 localization at the 5 ′ side that is closer to the premature termination codon. It has also been reported that hUPF1 binds directly to mRNA, with binding varying as a function of mRNA 3 ′ -UTR length (Hogg and Goff 2010;Kurosaki and Maquat 2013).…”
Section: Discussionmentioning
confidence: 96%
“…Although the premature termination of translation enhances the binding of steady-state UPF1, which is largely hypophosphorylated (i.e. yet to be activated by SMG1-mediated phosphorylation), to the downstream 3′UTR (Kurosaki and Maquat, 2013;Lee et al, 2015), recent biochemical and transcriptome analyses have revealed that steady-state UPF1 associates with regions of cellular RNAs that are physically accessible to its binding, independently of translation. These RNAs include canonically defined NMD targets and also non-NMD targets, including long non-coding RNAs (Gregersen et al, 2014;Hogg and Goff, 2010;Hurt et al, 2013;Kurosaki and Maquat, 2013;Lee et al, 2015;Zünd et al, 2013).…”
Section: Translation Modulates Binding Of Human Upf1 To Cellular Mrnasmentioning
confidence: 99%